Resveratrol exerce efeito neuroprotetor em animais parkinsonianos via inibição da inflamação e aumento da proteína transportadora de dopamina (DAT) - Mendonça, Ana Paula Fontenele Menezes (2017)
Parkinson's disease (PD) is a neurodegenerative movement disorder, affecting 1% of the 65-year population and increasing to 4 to 5% after 85 years. PD is characterized clinically by resting tremor, akinesia, rigidity and postural instability and it has already been demonstrated that oxidative stress is involved in the pathophysiology of the disease. Resveratrol is a phytoalexin that has been described as having antioxidant and anti-inflammatory properties, with neuroprotective action in experimental parkinsonism. The objective of this study was to investigate the mechanism of neuroprotective action of resveratrol on the behavioral, biochemical and molecular changes induced by 6-hydroxydopamine (6-OHDA), an animal model of parkinsonism. Male Wistar rats (180-240 g) received 6-OHDA injections (18 μg / 3 μl) in the right striatum through stereotactic surgery and were treated resveratrol (50 mg / kg). We observed that parkinsonian animals presented deficits in motor behavior, balance, memory and olfactory discrimination. Resveratrol was able to protect these animals from motor deficits, memory, learning and olfactory disbility. Parkinsonian animals also had depressive behavior with the reduction of monoamines (dopamine, serotonin and naradrenaline) in the injured striatum and substantia nigra. This effect was totally reversed by resveratrol at the dose tested, with the prevention of depressive behavior in animals and the reestablishment of normal doses of monoamines. We were also able to prove that resveratrol prevented the death of the dopaminergic neurons in the substantia nigra (TH and FluorojadeC) as well as the decrease of the dopamine transporters (DAT) and D2. The inflammation is directly related to the pathogenesis of PD. In our model we can observe an increase in astrogliosis (GFAP), microgliosis (CD11-b), cyclooxygenase-2 (COX-2), IL-1β and apoptotic action (GSK-3β). Resveratrol presented a protective effect on the inflammatory response, preventing the increase of the atrocites, microglia, COX-2 and apoptosis. This suggests resveratrol exerts a neuroprotective effect on parkinsonism induction in rats, probably due to its anti-inflammatory and antiapoptotic action.